Literatur Review: Nilai Profetik Pada Metode Kisah Dalam Pendidikan Islam - Abdul Khalim; Abdul Kadir Badjuber; Abdul KFahrudin Majid; Rahmi Ifada; Siti Rosidah; Rahmat Budi Susetyo; Budi Hadriyanto (Diversity: Jurnal Ilmiah Pascasarjana, 2023)
The implementation of the kisah method in Islamic education is still equated with the storytelling method or fairy tales. Even though the kisah method is a method from the Qur'an that have multiple values. The purpose of this research is to reveal the prophetic values ​​of the kisah method. This study uses the qualitative method with a systemic literature review. The results showed that the kisah method contains prophetic values, 1) shidq; is the content of the story is true, the lesson of the story is true and it is intended to strengthen faith, 2) amânah; is the macth between the facts and the story, be able to master the content of the story both its advantages and disadvantages, understanding the contents of the story and the lessons, 3) tabligh; appropriate use of words and diction according to the listener, understands storytelling techniques and develops dynamically in the use of infrastructure, is fair without exaggerating leading to superstition and does not reduce and change the contens of the story so as to cause slander, balanced in gentleness and firmness, 4) faṯânah; choose the right lesson, do not enter into khilafiyah tanazzu' (differences that lead to divisions) ordinarily in khilafiyah fiqhiyyah (differences due to understanding), main and branch understandings.